How to see - Hanh, Thich Nhat. (London : Rider, 2019)
Thich Nhat Hanh brings his signature clarity, compassion and humour in showing us how to achieve an awakened, more relaxed state of self-awareness so we cn understand ourselves and the world around us.
Keywords: Mindfulness (Psychology).; Self-consciousness (Awareness).; Buddhist meditations